Characteristics of patients visiting naturopathic practitioners for maternal and reproductive health. (30th September 2020) - Steel, A; Foley, H; Schloss, J; Redmond, R
Abstract: Background: Naturopathy, recognised by the World Health Organisation as a European traditional medicine system, is practiced in every world region. Patients in countries where naturopathy is practiced visit a naturopathic practitioner for a range of health concerns including maternal and reproductive health; recognised as a global health priority area. This study aims to examine the characteristics of patients visiting naturopathic practitioners for their maternal and reproductive health concerns, and the clinical care provided by naturopathic practitioners to those patients. Methods: An international cross-sectional survey of typical naturopathic practices and their associated patients, conducted in naturopathic clinics in 14 countries and 4 world regions. Naturopathic practitioners(n = 54) were invited to prospectively complete an online survey for up to 20 consecutive cases within the study period. Univariate relationships were examined through chi-square tests. Backwards stepwise logistic regression was employed to explore the characteristics most likely to be associated with individuals visiting a naturopath for maternal and reproductive health. Results: Naturopathic practitioners provided data for 852 patients, with 43 (5.0%) visiting a naturopath for maternal and reproductive health concerns such as fertility (54.8%), pregnancy (26.2%), preconception health (11.9%), and lactation, breastfeeding or other postnatal care (7.1%). The regression analysis indicates the practitioners are more likely to prescribe acupuncture (OR 2.71, p<.001) and more likely to identify gynecological (OR 4.31, p<.001) or endocrine (OR 3.30, p=.01) systems as important in the management of the health of these patients. Conclusions: Individuals are accessing naturopathic practitioners for maternal and reproductive health. An examination of the motivations influencing this population to access naturopathic care and the outcomes of this care is urgently needed. Key messages: Naturopathic practitioners throughout the world are being visited for assistance with maternal and reproductive health issues including fertility, pregnancy, preconception and postnatal care. Naturopathic practitioners are prescribing acupuncture, as well as a wide range of other treatments, for maternal and reproductive health issues.